2021
DOI: 10.47352/jmans.v1i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Green Chemistry Influences in Organic Synthesis : a Review

Abstract: Environmental pollution and global warming cause serious problems in human life. Since the demand for our human daily appliances had been increased by years, the organic chemical-based industries response that demand increment by increasing their production process. Because of that, the environmental pollution becomes worse and worse. Green chemistry thus was introduced to influence the chemical industries to strive for better environmental sustainability. Over 20 years, green chemistry principles have to infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 54 publications
(51 reference statements)
1
35
0
Order By: Relevance
“…Complex C1: Isolated as white powder in 85 % yield (853.2 mg, 0.992 mmol). 1 H-NMR (400 MHz, CDCl 3 , 298 K): δ/ppm = 9.0 (s,1H, NÀ H), 7.70 (dd, J = 5.7 Hz, 1.7 Hz, 2H), 7.50 (ddd, J = 8.9 Hz, 7.2 Hz, 1.9 Hz, 2H), 7.36 (d, J = 8.3 Hz, 2H), 7.34-7.26 (m, 6H), 7.23 (t, J = 7.5 Hz, 8H), 7.13 (dt, J = 7.1 Hz, 5.0 Hz, 8H), 7.06-6.98 (m, 4H), 6.91-6.85 (m, 2H), 6.48 (t, J = 6.4 Hz, 2H). 13 C{ 1 H} NMR (100 MHz, CDCl 3 , 298 K): δ/ppm = 157.8 (t, J C-P = 6.2 Hz), 153.8, 147.1, 138.7, 134.3, 133.2 (t, J C-P = 8.2 Hz), 131.7, 131.1 (t, J C-P = 16.0 Hz), 129.9, 128.7 (t, J C-P = 4.7 Hz), 125.0, 124.6 (t, J C-P = 13.1 Hz), 120.1, 116.8, 115.8.…”
Section: Synthesis Of the Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complex C1: Isolated as white powder in 85 % yield (853.2 mg, 0.992 mmol). 1 H-NMR (400 MHz, CDCl 3 , 298 K): δ/ppm = 9.0 (s,1H, NÀ H), 7.70 (dd, J = 5.7 Hz, 1.7 Hz, 2H), 7.50 (ddd, J = 8.9 Hz, 7.2 Hz, 1.9 Hz, 2H), 7.36 (d, J = 8.3 Hz, 2H), 7.34-7.26 (m, 6H), 7.23 (t, J = 7.5 Hz, 8H), 7.13 (dt, J = 7.1 Hz, 5.0 Hz, 8H), 7.06-6.98 (m, 4H), 6.91-6.85 (m, 2H), 6.48 (t, J = 6.4 Hz, 2H). 13 C{ 1 H} NMR (100 MHz, CDCl 3 , 298 K): δ/ppm = 157.8 (t, J C-P = 6.2 Hz), 153.8, 147.1, 138.7, 134.3, 133.2 (t, J C-P = 8.2 Hz), 131.7, 131.1 (t, J C-P = 16.0 Hz), 129.9, 128.7 (t, J C-P = 4.7 Hz), 125.0, 124.6 (t, J C-P = 13.1 Hz), 120.1, 116.8, 115.8.…”
Section: Synthesis Of the Compoundsmentioning
confidence: 99%
“…One of the long-standing goals in organic chemistry has been the search for new synthetic routes that are sustainable, avoid toxic reagents, and exploit renewable energy sources in order to meet the requirements of green chemistry. [1] Within this context, a promising alternative to the thermal initiation of reactions has been the use of visible light as a mild and selective source for activating organic molecules. [2] However, most of the organic substrates only absorb in the ultraviolet (UV) region, and for this reason, photosensitizers and photoredox catalysts capable of absorbing energy in the visible region have been developed to trigger the desired reaction on given organic substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, biodesulfurization offers a low capital cost process, valuable by‐products (2‐hydroxybiphenyl and 3‐hydroxy‐2‐formylbenzothiophene), fewer greenhouse gases emission, and a selective process; thus, the physicochemical properties of crude oil are not significantly influenced 160 . Because of that, the biodesulfurization process is considered as a “green” desulfurization method for today's world 6,161 . However, the biodesulfurization process occurs through a very slow kinetic with very strict operation conditions (pH, temperature, dissolved oxygen, viscosity, etc.)…”
Section: Biodesulfurizationmentioning
confidence: 99%
“…However, currently, crude oil still remains irreplaceable for several industrial processes. In 2019, around 80% of world energy was generated from the usage of fossil fuel, i.e ., crude oil (37%), natural gas (32%), and coal (11%), while the renewable energy (11%) and nuclear electric power (8%) are only used in a limited way 6 …”
Section: Introductionmentioning
confidence: 99%
“…All components of M. oleifera, including the leaves, flowers, seeds, pods, and roots have been evaluated [5][6][7][8][9][10]. It was reported that the dry leaves contain a large amount of macro and micronutrients (protein 29.4 percent, fat 5.2 percent, calcium 21.85 mg • g -1 , phosphorus 2.52 mg • g -1 , magnesium 4.48 mg • g -1 , iron 2.56 mg • g -1 , potassium 12.36 mg • g -1 , vitamin B complex 3.11 mg • g -1 , vitamin C 1.58 mg • g -1 , vitamin E 1.10 mg • g -1 ) [11,12]. Furthermore, it also contains a lot of natural products such as tannins, sterols, saponins, terpenoids, phenolics, alkaloids and flavonoids like quercetin, isoquercitrin, kaemfericitin, isothiocyanates, and glycoside compounds [13][14][15].…”
Section: Introductionmentioning
confidence: 99%